The Use of Jigsaw to Improve the Student's Vocabulary for The Eight Year Students of MTs Miftahul Ulum - Khoirul Umam Muzayyanah (Medan Resource Center, 2021)
Abstract Vocabulary is an essential means in conducting communication. Developing students’ vocabulary is one of the important tasks for English teachers. The researcher as a teacher used jigsaw as a technique in teaching vocabulary. Mastering English vocabularies is the first key to master English well. Jigsaw strategy is an efficient way to learn the course material in a cooperative learning style. The purpose of this research is to improve the students’ vocabulary using jigsaw. This is a classroom action research. The result shows that after implementing the jigsaw, the students’ vocabulary had a strong improvement. The students’ improvement can be seen from the students’ participation during the lesson and their score. The use of jigsaw had given a positive effect to the students’ vocabulary ability. The effect was not only for their vocabulary but also for their motivation and their interest to English.